The Qibla Direction of the Great Mosque Inherited from the Islamic Kingdom in Java: Myth and Astronomy Perspective - Sabiq, Fairuz (ADDIN, 2019)
The determination of the direction of the qibla at the Great Mosque that was inherited from the Islamic Kingdom of Java had executed by waliyullah. Through the folklore and history of the Land of Java or known as a Babad, those stories explained that waliyullah was the person who determining direction of Qibla by raising his right-hand and holding Masjidil Haram in Makkah. On the other hand, he was holding mustoko of the mosque. A line between his right and left-hand as a line of direction of the mosque’s Qibla. This kind of story was widespread in society as a myth. This myth was related to karomah (divine distinction) of waliyullah. Therefore, Qibla of the mosque could not be changeabled, eventhough, the qibla direction of Great Mosque is not unidirectional with direction of Masjidil Haram. People’s opinions said that Qibla direction of the mosque is right according to jihatul Ka’bah. This research is integrated with myth and astronomy. The results of this research are different from formerly perspectives. Firstly, ulama received the result of myth but they were not catching messages of the myth. Ulama were only understood of the explicit meanings of the myth but they were not understand of the implicit meanings of the myth. Secondly, Sunan Kalijaga had determined direction Qibla of the Mosque with his knowledge about falak, he was not doing it by only his karomah (divine distinction). Thirdly, the direction of the Qibla at the Great Mosque that was inherited from the Islamic Kingdom of Java was determined its Qibla direction by using ‘ainul Ka’bah method and not only by using jihatul Ka’bah method. The last, Java society has a feodalistic character.